Overview of Governance and Rampant Corruption in Land Administration in Bangladesh - Chowdory , Mohammad Moin Uddin (South Asian Journal of Social Sciences and Humanities, 2024)
This study focuses on the governance and corruption in the land management system of  Bangladesh and the effect of these factors on the tenure security of land and the country’s  economic growth. This study used a quantitative research design. The research outcomes show  that corruption is systematic in all levels of land management, thus eroding the security of  tenure, and worsening social inequalities. The new governance reforms have also been  implemented to curb corruption; however, these changes’ impact has been rather poor. In light  of the findings of the study, there is a well-established need for systematic reform to improve  the situation in Bangladesh through digitization of land records, better transparency, and higher  accountability in the land administration sector. The investigation presented in this research  adds to the discussion of governance and development and offers practical policy suggestions  that relate to fighting corruption and enhancing the efficient utilization of Bangladeshi land.
Keywords: Rampant Corruption; Land Administration